Quality of E-Learning Learning During the Covid-19 Pandemic - Despa Wandri; Nizwardi Jalinus (Jurnal Ilmiah Pendidikan Profesi Guru, 2022)
Along with the increasing number of vocational schools in Indonesia, the global market demands for the quality of its graduates are also increasing. The evaluation of the quality of learning is still low. The evaluation carried out is still a formality so that it has not had an impact on subsequent activities, and the level of satisfaction of students and parents as customers is not yet known. This study aims to evaluate and reveal aspects of the quality of learning during the COVID-19 pandemic. This evaluation study uses the CIPP model with a quantitative method approach. The population is class XI students, totaling 148 people. Data collection techniques using questionnaires or questionnaires supported by data interviews and documentation. The results of the questionnaire obtained were analyzed using the technique of the percentage of respondents' level of achievement. The results showed that the average acquisition of the questionnaire on the Context, Input, Process, Product, and Outcome variables were 73.7%, 76.8%, 79.9%, 79.4% in the Fairness category. So it can be concluded that the quality of learning is categorized as quite good. With the results of this study, schools can determine the performance of each aspect of learning. It is recommended for schools to improve the quality of learning and performance in all aspects to provide excellent service for students and parents.